DETERMINATION OF HARDWARE OF SOFTWARE DEVELOPMENT - Берков, Юрий; Левченко, Андрей; Руденко, Юрий (SWorldJournal, 2021)
In software product development, it is important to evaluate the resources expended that have been invested in the project. And one of the important criteria for evaluating the product is the complexity of development. The calculation given in this artic